Louceiras do Maruanum (Amapá): estratégia educativa para a conservação da tradição do criar-saber-fazer ceramista - COSTA, Célia Souza da (2020)
The creation-know-how of Maruanum pottery is a ceramic tradition passed down from generation to generation that is part of the quilombola communities of Santa Luzia and Carmo do Maruanum, Maruanum District, Macapá municipality, State of Amapá. Some studies already carried out, as is the case of Coirolo (1991) and Costa (2014), indicate that the tradition of Maruanum pottery is on the brink of extinction, children and young people in the communities are not learning this pottery craft. Thus, the elaboration of this thesis had as its central problem: how the pottery and teachers of Maruanum, as well as external cultural managers represent the ceramic tradition (pottery from Maruanum) and how the strategy of the Paulo Freire Culture Circle can contribute to conservation of the ceramic tradition? The general objective of this thesis was: to analyze the possible representations of the pottery and teachers of Maruanum and also of the external cultural managers about the ceramic tradition (pottery of Maruanum). The methodology used was a qualitative, ethnographic, exploratory, descriptive approach with participant observation. Data collection was carried out using questionnaires, forms and open interviews. Thirteen china makers, 07 teachers and 04 cultural managers participated in this study. The answers attributed by the research participants were systematized in the Cmap Tools software, which generated concept maps analyzed from the theoretical contribution of Social Representations and content analysis by Bardin (2016). Authors such as: Arruti (2006,2005,2003); Freire (2013,2016,2017,2018); Boneti (2011,2018); Gohn (2006, 2016); Loureiro (2012,2014); Maturana (2018); Scifoni (2015,2017); Florêncio (2014,2015) make up the theoretical corpus of the thesis. The study concluded that the representations of Maruanum pottery and teachers and also of external cultural managers are differentiated. and that these possible representations are important because they serve as a parameter for the elaboration of public policies and educational interventions. For the chinaware, the ceramic tradition has an identity, community and kinship sense; the teachers see Maruanum dishes as a tradition and culture that is part of the community and needs to be addressed in the classroom; cultural managers believe that the ceramics profession is unique, a culture of resistance that needs preservation. Observations and interviews pointed out that there are no consolidated educational environmental heritage education actions in Maruanum. From the data presented by the analysis of social representations, the thesis presented an educational strategy based on the Paulo Freire Culture Circle; proposed the academic use of the term create-know-how; and the inclusion of patrimonial education as part of the environmental education that originated the term Patrimonial Environmental Education (EAP).